IMPLEMENTATION OF VILLAGE BUSINESS MANAGEMENT BOARD (BUMDes) CIBALANARIK KECAMATAN TANJUNGJAYA TASIKMALAYA DISTRICT - Deni Sudrajat; Tine Badriatin (LPM Universitas Pasundan, 2019)
This study aims to determine and analyze the implementation of the management of the Cibalanarik Village-Owned Enterprises of Tanjungjaya District, Tasikmalaya Regency. The implementation can be seen from the factors of policy size and objectives, resources, characteristics of implementing agents, disposition of implementers, communication between organizations and implementing activities. The research method used is qualitative methods through observation and in-depth interviews with people who have information related to the management of the Cibalanarik Village-Owned Enterprises in the Tanjungjaya District of Tasikmalaya Regency. Data analysis technique is done through data reduction, data display up to the conclusion. Based on the results of the study showed that the implementation of the management of the Entrepreneurship of the Village of Cibalanarik, Tanjungjaya District, Tasikmalaya Regency. Implementation can be effective by fulfilling aspects of achieving policy objectives, availability of resources, the ability of the implementers / managers of Village-Owned Enterprises, the spirit required to build and develop Village-Owned Enterprises, and the ability to communicate with various parties.